Legal Services and the Determination of the Indonesian Standard Industrial Classification for Green Hydrogen Investment in Supporting Sustainable Investment in Indonesia - Sang Ayu Putu Rahayu; Rahayu Fery Anitasari; Dina Silvia Puteri; Asrul Ibrahim Nur; Dhita Widya Putri (Universitas Negeri Semarang, 2026)
Indonesia has significant potential for green hydrogen investment, driven by new and renewable energy (NRE) sources such as geothermal, solar, and hydropower, with projected demand reaching 2–5 million tons per year by 2040. This sector is particularly strategic for industrial decarbonization and heavy-duty transportation, with an investment target of US25.2 billion (Rp395.58 trillion) by 2060. This potential presents opportunities for Indonesia to develop green hydrogen as a future energy pillar derived from renewable energy sources with zero carbon emissions, supporting the decarbonization of the heavy industry and transportation sectors. However, the realization of investment activities is intrinsically linked to licensing mechanisms and regulatory frameworks. In this context, legal certainty and the establishment of the Indonesian Standard Industrial Classification (KBLI) are crucial for facilitating business licensing and providing regulatory clarity for investors. The absence of a specific KBLI code for green hydrogen investment may engender legal uncertainty and administrative barriers that potentially impede investment realization. Therefore, determining a specific KBLI for green hydrogen investment is imperative to ensure legal certainty, strengthen the investment climate, and enhance investor confidence, thereby supporting sustainable investment in Indonesia. Establishing a clear regulatory framework through appropriate KBLI classification will not only provide legal certainty for the substantial capital injected but also create an incentive structure that attracts profit-oriented investments in this sector and enhances its economic viability. Ultimately, green hydrogen investment is not only economically beneficial but also a strategic sector for the advancement of clean, renewable, and environmentally friendly energy in Indonesia.